1997
DOI: 10.1104/pp.113.4.1059
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Matrix Assembly in Diatoms (Bacillariophyceae) (I. A Model of Adhesives Based on Chemical Characterization and Localization of Polysaccharides from the Marine Diatom Achnanthes longipes and Other Diatoms)

Abstract: Extracellular adhesives from the diatoms Achnanthes longipes, Amphora coffeaeformis, Cymbella cisfula, and Cymbella mexicana were characterized by monosaccharide and methylation analysis, lectin-fluorescein isothiocyanate localization, and cytochemical staining. Polysaccharide was the major component of adhesives formed during cell motility, synthesis of a basal pad, and/or production of a highly organized shaft. Hot water-insoluble/hot 0.5 M NaHC0,-soluble anionic polysaccharides from A. longipes and A. coffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
179
1
4

Year Published

2003
2003
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(195 citation statements)
references
References 24 publications
(41 reference statements)
9
179
1
4
Order By: Relevance
“…Cell disruption was often assisted by lyophilization of the diatoms or, in the study of chrysolaminaran from P. tricornutum, by pulverizing frozen cells (Ford & Percival, 1965). Compositional and structural analyses confirmed that chrysolaminaran was the dominant component extracted by these methods (Ford & Percival, 1965;Handa, 1969;Handa & Tominaga, 1969;Handa & Yanagi, 1969;Myklestad & Haug, 1972;Smestad Paulsen & Myklestad, 1978;Wustman et al, 1997).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Cell disruption was often assisted by lyophilization of the diatoms or, in the study of chrysolaminaran from P. tricornutum, by pulverizing frozen cells (Ford & Percival, 1965). Compositional and structural analyses confirmed that chrysolaminaran was the dominant component extracted by these methods (Ford & Percival, 1965;Handa, 1969;Handa & Tominaga, 1969;Handa & Yanagi, 1969;Myklestad & Haug, 1972;Smestad Paulsen & Myklestad, 1978;Wustman et al, 1997).…”
mentioning
confidence: 99%
“…willei), Chaetoceros sp., Skeletonema costatum and Stauroneis amphioxys (Ford & Percival, 1965;Handa & Yanagi, 1969;Myklestad & Haug, 1972;Smestad Paulsen & Myklestad, 1978;McConville et al, 1986). More recently, linkage analyses of water extracts obtained during sequential extraction of Achnanthes longipes (Wustman et al, 1997) and Pinnularia viridis (Chiovitti et al, 2003) yielded 1,3-linked glucopyranose (Glcp) as the dominant component.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…As with bacteria, EPS produced by different types of diatoms are diverse [49,50], and include various protein fractions and complex anionic polysaccharides with heterogeneous combinations of monosaccharide [45]. In addition, at least two types of mucilage can be detected for the same species of diatom [51,52].…”
Section: Microalgae Adhesionmentioning
confidence: 99%